SEBUAH TINJAUAN LITERATUR TERHADAP PENELITIAN RELEVANSI NILAI SETELAH ADOPSI IFRS - Manuela, Angel; Septiani, Leny; Wulan, Ariska Berlian Nur; Fitria, Salsha Ramadhani Nur (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2021)
The purpose of this study is to provide an overview of value relevance (VR) by reviewing and analyzing research on VR that has been conducted mainly in Indonesia. The structured literature review (SLR) method was used to track the development of the VR literature. The keywords used in this study are “adopsi IFRS”,